High‐quality evergreen azalea genome reveals tandem duplication‐facilitated low‐altitude adaptability and floral scent evolution. Issue 12 (21st August 2021) - Wang, Xiuyun; Gao, Yuan; Wu, Xiaopei; Wen, Xiaohui; Li, Danqing; Zhou, Hong; Li, Zheng; Liu, Bing; Wei, Jianfen; Chen, Fei; Chen, Feng; Zhang, Chengjun; et al.
Summary: Azalea belongs to Rhododendron, which is one of the largest genera of flowering plants and is well known for the diversity and beauty in its more than 1000 woody species. Rhododendron contains two distinct groups: the most high‐altitude and a few low‐altitude species; however, the former group is difficult to be domesticated for urban landscaping, and their evolution and adaptation are little known. Rhododendron ovatum has broad adaptation in low‐altitude regions but possesses evergreen characteristics like high‐altitude species, and it has floral fragrance that is deficient in most cultivars. Here we report the chromosome‐level genome assembly of R. ovatum, which has a total length of 549 Mb with scaffold N50 of 41 Mb and contains 41 264 predicted genes. Genomic micro‐evolutionary analysis of R. ovatum in comparison with two high‐altitude Rhododendron species indicated that the expansion genes in R. ovatum were significantly enriched in defence responses, which may account for its adaptability in low altitudes. The R. ovatum genome contains much more terpene synthase genes ( TPSs ) compared with the species that lost floral fragrance. The subfamily b members of TPS are involved in the synthesis of sesquiterpenes as well as monoterpenes and play a major role in flora scent biosynthesis and defence responses. Tandem duplication is the primary force driving expansion of defence‐responsive genes for extensive adaptability to the low‐altitude environments. The R. ovatum genome provides insights into low‐altitude adaptation and gain or loss of floral fragrance for Rhododendron species, which are valuable for alpine plant domestication and floral scent breeding.